2022
DOI: 10.2147/rmhp.s359733
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Neutrophil to Lymphocyte Ratio, The Platelet to Lymphocyte Ratio, and Cardiac Syndrome X

Abstract: Objective This study aims to investigate the relationship between the neutrophil to lymphocyte ratio (NLR), the platelet to lymphocyte ratio (PLR), and cardiac syndrome X (CSX). Methods A total of 102 patients with CSX who were hospitalized in the Cardiology Department of our hospital from December 2018 to December 2020 were enrolled in the CSX group, and 102 subjects who underwent physical examinations during the same period were included in the control group. An autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Pathologically, blood neutrophils increase, and lymphocytes decrease in response to inflammatory stress, increasing the NLR. PLR, similar to NLR, is a relatively novel inflammatory marker, with recent studies showing significant elevation in several cardiac disorders [ 34 ]. For example, a recent meta-analysis published in 2024 showed that among heart failure patients, PLR was significantly lower in survived patients rather than deceased group [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathologically, blood neutrophils increase, and lymphocytes decrease in response to inflammatory stress, increasing the NLR. PLR, similar to NLR, is a relatively novel inflammatory marker, with recent studies showing significant elevation in several cardiac disorders [ 34 ]. For example, a recent meta-analysis published in 2024 showed that among heart failure patients, PLR was significantly lower in survived patients rather than deceased group [ 35 ].…”
Section: Introductionmentioning
confidence: 99%